Research on Key Factors and Their Interaction Effects of Electromagnetic Force of High-Speed Solenoid Valve - Peng Liu; Liyun Fan; Qaisar Hayat; De Xu; Xiuzhen Ma; Enzhe Song (The Scientific World Journal)
Analysis consisting of numerical simulations along with lab experiments of interaction effects between key parameters on the electromagnetic force based on response surface methodology (RSM) has been also proposed to optimize the design of high-speed solenoid valve (HSV) and improve its performance. Numerical simulation model of HSV has been developed in Ansoft Maxwell environment and its accuracy has been validated through lab experiments. Effect of change of core structure, coil structure, armature structure, working air gap, and drive current on the electromagnetic force of HSV has been analyzed through simulation model and influence rules of various parameters on the electromagnetic force have been established. The response surface model of the electromagnetic force has been utilized to analyze the interaction effect between major parameters. It has been concluded that six interaction factors including working air gap with armature radius, drive current with armature thickness, coil turns with side pole radius, armature thickness with its radius, armature thickness with side pole radius, and armature radius with side pole radius have significant influence on the electromagnetic force. Optimal match values between coil turns and side pole radius; armature thickness and side pole radius; and armature radius and side pole radius have also been determined.